(untitled) (Research, Society and Development, 2021)
Objective: demonstrate how the use of mobile technological resources can help in the care of patients with tegumentary leishmaniasis (TL). Methods: this is an integrative review with a qualitative approach, with a bibliographic survey of publications carried out between 2017 and 2021 was carried out, in the LILACS, MEDLINE and SciELO databases, as well as in the Google Scholar virtual library. Results: the final sample of this review consisted of eight publications, four of which were carried out in Brazil. Some studies showed the development of mobile applications such as LeishCare® and Leish Heal, while others addressed the use of software systems that enable the monitoring of patients’ injuries throughout treatment through photographs. The creation of databases for dermatological subjects and the use of common communication tools that already exist on smartphones connected to the internet, such as messaging apps that allow the sending of images, email, social networks also demonstrated how these features technological devices can help in the care of patients with TL. Conclusion: the importance of new investigations in this area is observed, mainly in Brazil and in regions considered endemic, aiming at monitoring, treating and improving the quality of care and treatment of leishmaniasis.